Aktivitas fisik dan konsumsi camilan pada remaja obesitas - Mellia Silvy Irdianty; Toto Sudargo; Mohammad Hakimi (Berita Kedokteran Masyarakat (BKM), 2016)
Physical activities and snack consumption of rural and urban obese adolescents in Bantul PurposeThis study to determine the difference of physical activity and snack consumption in adolescent obesity in urban and rural areas in the district of Bantul.MethodThis study used a case control study design, with a population of high school teenagers in Bantul. Cases are obese adolescents who were diagnosed at screening, while the control is not obese adolescents. Data analysis included univariable consist of frequency distribution, bivariable consist of chi-square and t-test and also logistic regression test for mulitivariabel analysis.ResultsAdolescents who do light physical activities are more likely have obesity almost 5 times than those who do physical activity in normal. Kind of snack and obesity have correlation in statistic and practical, which is many research prove that obesity found 2 times than adolescents who consume fried foods.ConclusionThere are differences of mean in snack weight and snack intake in obese adolescents. The low physical activity, high snack frequency, type of fried foods, snack weight, and snack intake are most likely to increase the incidence of obesity.